Essential habitats for pre-recruit Octopus vulgaris along the Portuguese coast - Moreno, A.
The exploitation of the common octopus Octopus vulgaris in Portugal increased 50% in the last 20 years, largely motivated by the depletion of many fish stocks. Recently, the biomass of this fishery resource sharply decreased in some areas causing serious concern among local fishermen and an effort is underway to advise on novel and sustainable management measures. In this context, the octopus pre-recruit aggregations along the Portuguese coast are identified using georeferenced fishery-independent data, from autumn and winter sampling between 1996 and 2008. The relationships between pre-recruit aggregations and several environmental variables are analyzed to characterize their essential habitats (EFH). Pre-recruits are distributed throughout the Portuguese coast aggregated in 8 distinct recruitment grounds located on the middle-shelf at 11-19. km from the coastline, which are characterized by average bottom depths of 65-110. m and are associated to major rivers and lagoon systems. Within each season pre-recruit abundance is much higher in the south region, while pre-recruit aggregations on the northwest coast showed high inter-annual and seasonal variation driven by environmental variability. The western zone adjacent to Ria Formosa lagoon (southern coast) was identified as the main recruitment ground for O. vulgaris along the Portuguese coast. This is supported by the higher abundance of pre-recruits and by the recurrence of their presence in this area over the years analyzed, both in autumn and winter. The effects of physical variables on pre-recruit abundance modelled with generalized additive models (GAM) showed important regional differences. Bottom salinity and river runoff are the environmental variables that have most impact on pre-recruit distribution and abundance on the west coast, regardless of any seasonal effects. On the other hand, temperature imposes distinct seasonal and regional limitations on pre-recruit distribution, both on the NW and S regions. Pre-recruit preferential habitat is characterized by bottom temperatures of 14. °C, salinity values around 36.0, low precipitation (average <200. mm), and coarse sediments (in which they find shelters to escape predation). Some of the octopus recruitment grounds identified are located in areas under intense fishing pressure, both by artisanal fisheries using traps and by bottom trawling. Thus, their value for the sustainability of the octopus fishery should be taken into consideration in future marine management strategies.